Effect of silane pretreatment on the immediate bonding of universal adhesives to computer‐aided design/computer‐aided manufacturing lithium disilicate glass ceramics. (24th February 2017) - Yao, Chenmin; Zhou, Liqun; Yang, Hongye; Wang, Yake; Sun, Hualing; Guo, Jingmei; Huang, Cui
Abstract : The aim of this study was to investigate the effect of silane pretreatment on the universal adhesive bonding between lithium disilicate glass ceramic and composite resin. IPS e.max ceramic blocks etched with hydrofluoric acid were randomly assigned to one of eight groups treated with one of four universal adhesives (two silane‐free adhesives and two silane‐containing adhesives), each with or without silane pretreatment. Bonded specimens were stored in water for 24 h. The shear bond strength (SBS) of the ceramic‐resin interface was measured to evaluate bond strength, and the debonded interface after the SBS test was analysed using field‐emission scanning electron microscopy to determine failure mode. Light microscopy was performed to analyse microleakage and marginal sealing ability. Silane pretreatment significantly and positively influenced SBS and marginal sealing ability. For all the universal adhesive groups, SBS increased and the percentage of microleakage decreased after the pretreatment. Without the pretreatment, SBS and the percentage of microleakage were not significantly different between the silane‐containing universal adhesive groups and the silane‐free groups. Cohesive failure was the main fracture pattern. The results suggest that additional silane pretreatment can effectively improve the bonding strength and marginal sealing of adhesives to lithium disilicate glass ceramics. The bonding performance of silane‐containing universal adhesives without pretreatment is similar to that of silane‐free adhesives.